Gresik's biodiversity: A potential learning resource to support Sustainable Development Goals 14 and 15 - Andini Dwi Cahyani; Ulfi Faizah; Dwi Anggorowati Rahayu; Reni Ambarwati; Agus Muji Santoso; Arum Nika Wiliagni (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2026)
Gresik has a diverse terrestrial and aquatic ecosystem that supports high biodiversity. However, the available biodiversity data remains fragmented and have not been optimally utilized as a contextual learning resource in biology education. This study aims to describe the biodiversity of Gresik and analyze its potential as a learning resource for biodiversity topics to support Sustainable Development Goals 14 and 15. A qualitative descriptive approach was employed through three integrated phases: (1) biodiversity inventory based on 394 student research reports from Animal Systematics courses conducted between 2021 and 2023; (2) a survey involving 31 senior high school biology teachers in Gresik using a validated questionnaire; and (3) a PRISMA-based literature review of articles published between 2017 and 2025. The results identified that Gresik’s biodiversity has 225 animal species from 7 groups of invertebrates and 2 groups of vertebrates spread across 10 types of ecosystems. Furthermore, 84% of teachers have utilized biodiversity in their teaching, but these activities are dominated by observation in the school environment. Literature review findings suggested that Outdoor Learning, Discovery Learning, Guided Inquiry, and Project-Based Learning are effective approaches for integrating Gresik’s biodiversity into lessons. This study contributes a synthesized biodiversity database for integrating local biodiversity into contextual biology learning, thereby strengthening environmental literacy, supporting the implementation of the Merdeka Curriculum and Deep Learning principles, and contributing to Sustainable Development Goals 14 and 15. Future studies are recommended to develop and evaluate biodiversity-based learning resources derived from the biodiversity potential of Gresik.